2013
DOI: 10.1371/journal.pone.0079096
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Association of N-Terminal Pro-B-Type Natriuretic Peptide with Metabolic Syndrome in Patients with Congestive Heart Failure

Abstract: BackgroundMetabolic syndrome has been shown to be associated with lower levels of plasma N-terminal pro-B-type natriuretic peptide (Nt-proBNP) in the general population. We sought to elucidate the relationship between Nt-proBNP and components of metabolic syndrome in patients with congestive heart failure (CHF).MethodsFasting blood samples were obtained from 93 patients in our institution. Plasma levels of Nt-proBNP and other biochemical data were measured. The New York Heart Association (NYHA) classification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
1
9
1
Order By: Relevance
“…Twenty-seven studies 20,21,2426,3134,38,39,41,43,48,49,51,5458,60–64,66 reported the association between cardiac NPs and TC, for a total of 43428 subjects evaluated. Twenty-eight studies 2025,2730,3234,3739,44,45,51,52,5557,59,61,63,64,66 reported the association between cardiac NPs and LDLc, for a total of 44829 subjects evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-seven studies 20,21,2426,3134,38,39,41,43,48,49,51,5458,60–64,66 reported the association between cardiac NPs and TC, for a total of 43428 subjects evaluated. Twenty-eight studies 2025,2730,3234,3739,44,45,51,52,5557,59,61,63,64,66 reported the association between cardiac NPs and LDLc, for a total of 44829 subjects evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-eight studies 2025,2730,3234,3739,44,45,51,52,5557,59,61,63,64,66 reported the association between cardiac NPs and LDLc, for a total of 44829 subjects evaluated. Thirty-six studies 20,21,2426,3134,38,39,41,43,48,49,51,5458,60–64,66 reported the association between cardiac NPs and HDLc, for a total of 49951 subjects evaluated. Thirty-nine studies 2030,3242,4447,5057,5964 reported the association between cardiac NPs and TG, for a total of 39649 subjects evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High BNP levels correlate with left ventricular dysfunction and its prognosis (Chang et al, 2013;Geske et al, 2013). However, high levels of BNP also have been found in congestive states such as heart and renal failure and in chronic liver disease (Passino et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Higher BNP levels are linked with poor outcome, worst prognosis and higher mortality rate [13]. The measured value correlates with severity of disease and its prognosis [14,15].…”
Section: Introductionmentioning
confidence: 99%